Perceptual training to increase drivers' ability to spot motorcycles at T-junctions. (July 2017) - Crundall, David; Howard, Aaron; Young, Angela
Highlights: Car drivers need to be trained to process motorcycles quickly to avoid Look But Fail To See errors. We trained a group of car drivers to visually discriminate between motorcycles using a Pelmanism card game. Trained drivers were subsequently better at spotting motorcycles in a T-junction task that a control group of car drivers. Abstract: Motorcyclists too often collide with other road users who pull out of side roads in front of them. These other road users typically report making all the necessary visual checks, despite failing to see the approaching motorcycle. These Look But Fail To See errors appear to be attenuated in road users who themselves have motorcycling experience, suggesting that motorcycle exposure may lower thresholds for spotting these vulnerable road users through natural perceptual learning. This raises the possibility that perceptual training could improve car drivers' abilities to spot motorcycles. Two experiments are reported. The first experiment demonstrated that a T-junction task, requiring participants to detect an approaching vehicle in briefly displayed images, was sensitive to participants' motorcycle experience, with dual drivers (who both ride motorcycles and drive cars) performing better than average car drivers. Following this, a second experiment split the car drivers into 2 groups. One group undertook a Pelmanism task requiring participants to match pairs of motorcycles, while the control group had to match pairs of fruit. When the two groups were re-tested on the T-junction task, the group who had undergone perceptual training for motorcycles via the Pelmanism task, were better able to identify approaching motorcycles, but not approaching cars. The results suggest that gamification of perceptual training for motorcycle detection provides a novel opportunity to improve driver safety.